Design and Build a Student Course Database Using Microsoft Access and Visual Basic.Net at the Guna Rayadi Ilmu Educational Foundation - Yonoriadi; Alfina (Journal Informatic, Education and Management (JIEM), 2025)
The advancement of technology is currently developing rapidly and becoming increasingly sophisticated, especially in the fields of information and applications, with many achievements already made by humans. Information technology has now become an inseparable part of human life. In this case, regarding the Design and Development of a Student Course Database Using Microsoft Access and Visual Basic. Net At the Guna Rayadi Ilmu Educational Foundation, which serves as a storage for data and information Learning and student activities software used for designing and planning is a simple programming language as a tool to help manage the database, which is expected to provide facilities and ease to the Management, Staff, and Instructors, to know the foundation's management data currently in use, as well as to fill out or print student and Instructor reports systematically and obtain complete information quickly through this program